Unplanned urbanization of Dhaka city: increase of rainfall induced flood vulnerability - Ali, Mirza Abdul (BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2006.